Study on Gear Broken Tooth in Fatigue Test of High Power Transfer Case - Ge Kai; Zhang Lei; Zhao Yanming; Shan Hongbo; Li Hongbiao; Zhang Bin; Gao Lili; Huo Chunjing (Jixie chuandong)
In the multi-axis super-heavy-duty test platform,the high-power transfer case has the problem of broken teeth during fatigue endurance. The comprehensive analysis is carried out on the failure gears,the causes of gear damage,such as gear strength,shaft and box stiffness,gear tooth profile and tooth orientation precision,surface heat treatment,etc. are analyzed one by one,and finally it is positioned as the gear tooth surface grinding burns,resulting in reduced hardness of the tooth surface,contact fatigue strength decreased,the occurrence of premature failure damage. In the improvement work,the grinding process of the gear tooth surface is modified,and 100% grinding burn monitoring is added. The improved high-power transfer case passed the fatigue endurance test.